Setting up a remote accessing of a PV plant and its analysis - Wei, W.H. (Asian Research Publishing Network, 2016)
The growing interest and increasing installation capacity of photovoltaic (PV) power plants have raised the awareness of the necessity and importance of better managing the PV power plant system in order to harvest the optimal energy yield from PV power plant. To accomplish the above objectives, sufficient supervision and monitoring the health and performance of the PV system are necessary. This paper presented a remote PV plant in UTP to be monitored remotely. The performance ratio of the PV power plant is evaluated based on the data collected through Sunny Portal. The result obtained shows that the low performance ratio of the PV power plant not only as a result of less power demand from the load but also due to the state of charge of the battery bank. The PR of the PV power plant varies between 12.90 and 29.74. Â© 2006-2016 Asian Research Publishing Network (ARPN).